2013
DOI: 10.1590/s1516-14392013005000164
|View full text |Cite
|
Sign up to set email alerts
|

Using fine recycled concrete aggregate for mortar production

Abstract: This research assessed the performance of mortars in which recycled concrete aggregates (RCA) was a component. It replaced natural sand but kept the same particle size distribution. Three mortars were produced with replacement ratios of 20%, 50% and 100% as well as a reference mortar containing no recycled aggregate. The compressive and flexural strength, water absorption by capillarity, drying capacity and susceptibility to cracking of these mortars were analyzed first. Then, based on these results, the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
89
5
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 151 publications
(129 citation statements)
references
References 12 publications
20
89
5
15
Order By: Relevance
“…Neno et al (19) found that the incorporation of 100% fine RCA resulted in a compressive strength improvement of 48.3% at 28 days of age, whereas in this study the total replacement of NA by fine RCA resulted in a decrease of 20.9%. Ledesma et al (20) described in detail the reasons for these differences.…”
Section: Compressive Strength Of Hardened Mortarcontrasting
confidence: 55%
See 4 more Smart Citations
“…Neno et al (19) found that the incorporation of 100% fine RCA resulted in a compressive strength improvement of 48.3% at 28 days of age, whereas in this study the total replacement of NA by fine RCA resulted in a decrease of 20.9%. Ledesma et al (20) described in detail the reasons for these differences.…”
Section: Compressive Strength Of Hardened Mortarcontrasting
confidence: 55%
“…Martínez et al (17) found lower densities in mortars manufactured with RA from CDW. Neno et al (19) showed a similar trend, although in that case the authors found a small increase with a 20% replacement ratio. The maximum losses observed by Neno et al (19) and in this study were similar (9.0% vs. 8.7%).…”
Section: Dry Bulk Density Of 28-day Hardened Mortarmentioning
confidence: 70%
See 3 more Smart Citations